Antibacterial activity of Tamarindus indica L. against bacteria causing urinary tract infection - Biswas, K; Sinha, SN (Journal of Bio-Science, 2018)
Urinary tract infection (UTI) is a common bacterial infection known to affect the different parts of the urinary tract of human which is a great menace for the last decade. Various medicinal plants have been reported for treating infectious diseases including UTI due to their fewer side effects and reduced toxicity. The present study was to investigate the antibacterial activity of Tamarindus indica against UTI causing pathogens. Bacteria were isolated from the UTI infected women patients and characterized by using biochemical and morphological methods. Acetonic, methanolic and chloroform leaf extracts were used to evaluate their antibacterial activity against the bacteria isolated from UTI infected patients and the zones of inhibitions were measured. Four bacteria viz. Escherichia coli, Pseudomonas aeruginosa, Klebsiella sp. and Enterococcus sp. were isolated from 60 urine samples infected with UTI. Regarding antibacterial susceptibility test ampicillin showed lowest degree of MIC against Pseudomonas aeruginosa and highest degree of MIC against Klebsiella sp. Acetone extract of Tamarindus indica leaves showed highest antibacterial activity against E. coli (22.5 mm). Methanol extract showed highest activity against Pseudomonas aeruginosa (21.4 mm) and chloroform extract showed highest activity against Klebsiella sp. (6.2 mm). Different phytochemicals found in the plant extract were alkaloids, tannins, flavonoids, sesquiterpenes, carbohydrates, saponins, phlobatannins and anthocyanins. J. bio-sci. 23: 47-55, 2015